Practicality of Guided Inquiry Learning Models Based on Critical Questions (Intersistatic) to Improve Students' Critical Thinking on Temperature and Heat Materials - Citron S. Payu; Ismail Pakaya; I Made Hermanto; Irsan Irsan; Muhammad Yunus (Jurnal Ilmiah Profesi Pendidikan, 2023)
The guided inquiry learning model is a learning model that is built based on learning concepts and connecting several concepts in the subject. This study aims to determine the practicality of the guided inquiry learning model based on critical questions (intersistatic) to improve critical thinking. This research method uses the Four D development model to define, design, develop, and disseminate. At the dissemination stage, a practicality test was carried out. The instruments used to measure practicality are observation sheets of the implementation of learning and questionnaires on the responses of model teachers and students. The limited testing results from applying the guided inquiry learning model based on critical questions to improve critical thinking have a very good level of practicality. In addition, applying learning models can trigger students' critical thinking skills. Therefore, the guided inquiry learning model based on critical questions can be implemented in learning to improve students' critical thinking.